Copper‐Catalyzed Oxidative Cross‐Coupling of P(O)‐OH Compounds with Aryl Boronic Acids. Issue 23 (16th August 2017) - Xiong, Biquan; Cheng, Qing; Hu, Chenghong; Zhang, Pangliang; Liu, Yu; Tang, Kewen
Abstract: A novel copper‐catalyzed oxidative cross‐coupling reaction of P(O)‐OH compounds with aryl boronic acids is illustrated. It is a simple way to generate a broad spectrum of functionalized O ‐aryl phosphinates, phosphonates, and phosphates from basic starting materials with moderate to excellent yields. Furthermore, a plausible mechanism has been proposed for the reaction. Abstract : A novel copper‐catalyzed aerobic cross‐coupling of P(O)‐OH compounds with aryl boronic acids is illustrated. It is a simple way to generate a broad spectrum of functionalized O ‐aryl phosphinates, phosphonates, and phosphates from basic starting materials with moderate to excellent yields.